Effectiveness of two methods for preparation of autologous platelet-rich plasma: an experimental study in rabbits - Nagata, Maria J. H. [UNESP]; Messora, Michel R.; Furlaneto, Flávia A. C.; Fucini, Stephen E.; Bosco, Alvaro F.; Garcia, Valdir G.; Deliberador, Tatiana M.; Melo, Luiz G. N. de (European Journal Of Dentistry, 2010)
The purpose of this study was to compare the quantity and quality of platelets in platelet-rich plasma (PRP) samples prepared using either the single- or the double-centrifugation protocol. Ten adult white New Zealand rabbits were used. Ten ml of blood were drawn from each animal via cardiac puncture. Each blood sample was divided into two equal parts for PRP preparation: 5 ml of blood were centrifuged according to a single-centrifugation protocol (Group I), and 5 ml were centrifuged according to a double-centrifugation protocol (Group II). Manual platelet counts were performed on the whole blood and PRP samples of each group. Smears were also done on all samples in order to see the morphology of the platelets. The data obtained in the manual platelet count were submitted to statistical analysis (repeated measures ANOVA, Tukey, P<.05). The average whole blood platelet count was 446,389/μl. The PRP samples in Group II presented an average platelet amount significantly higher than that of Group I (1,986,875 ± 685,020/μl and 781,875 ± 217,693/μl, respectively). The PRP smears from Group II were the only one to present platelets with altered morphology (75% of the smears). A few lymphocytes with increased cytoplasm were observed in the PRP smears of both Groups I (25% of the smears) and II (62.5% of the smears). Within the limits of this study, it can be concluded that the double-centrifugation protocol resulted in higher platelet concentrations than did the single-centrifugation protocol. However, the double-centrifugation protocol caused alterations in platelet morphology and was more sensitive to small processing errors.
Keywords: Blood; Centrifugation; Platelet count; Platelet-rich plasma